2014
DOI: 10.1186/s13071-014-0583-6
|View full text |Cite
|
Sign up to set email alerts
|

A semi-automated magnetic capture probe based DNA extraction and real-time PCR method applied in the Swedish surveillance of Echinococcus multilocularis in red fox (Vulpes vulpes) faecal samples

Abstract: BackgroundFollowing the first finding of Echinococcus multilocularis in Sweden in 2011, 2985 red foxes (Vulpes vulpes) were analysed by the segmental sedimentation and counting technique. This is a labour intensive method and requires handling of the whole carcass of the fox, resulting in a costly analysis. In an effort to reduce the cost of labour and sample handling, an alternative method has been developed. The method is sensitive and partially automated for detection of E. multilocularis in faecal samples.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
120
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 62 publications
(121 citation statements)
references
References 23 publications
(28 reference statements)
1
120
0
Order By: Relevance
“…The difference is also statistically significant ( P  < 0.001, Fisher’s test) when compared only to the two regions with an unknown status at study start (20/189, 10.6%, 95% CI: 6.6–15.9%). The national screening employed a newly designed magnetic-capture PCR [43] diagnostic technique with a reported sensitivity of 88% [43, 44], while the combined egg isolation and PCR technique used in this study has a lower reported sensitivity of 50% [45]. Thus, the difference cannot be explained by the diagnostic methods used.…”
Section: Discussionmentioning
confidence: 99%
“…The difference is also statistically significant ( P  < 0.001, Fisher’s test) when compared only to the two regions with an unknown status at study start (20/189, 10.6%, 95% CI: 6.6–15.9%). The national screening employed a newly designed magnetic-capture PCR [43] diagnostic technique with a reported sensitivity of 88% [43, 44], while the combined egg isolation and PCR technique used in this study has a lower reported sensitivity of 50% [45]. Thus, the difference cannot be explained by the diagnostic methods used.…”
Section: Discussionmentioning
confidence: 99%
“…Conventional-PCR or Multiplex-PCR withsieving procedure for egg isolation from faeces: 40-80 samples depending on taeniid prevalence (for procedures see Mathis et al, 1996;Trachsel et al, 2007); Nested-PCR for total DNA isolation from faeces: around 70 samples (for procedures see Monnier et al, 1996;Dinkel et al, 1998;Van der Giessen et al, 1999); Real Time-PCR for total DNA isolation from faeces: 70 samples (for procedures see Dinkel et al, 2011;Knapp et al, 2013); MC-PCR with manual DNA fishing from faeces: 70 samples (for procedures see ; MC-PCR with automated DNA fishing from faeces: 240 samples (for procedures see Isaksson et al, 2014).…”
Section: Shaking In a Vessel Technique (Svt) -Post Mortem Testmentioning
confidence: 99%
“…Before treatment with praziquantel, faecal samples were collected from the dogs. Mitochondrial DNA was extracted directly from the faecal material [3] because the small size of the samples did not allow isolation of parasite eggs. A fragment of mitochondrial ribosomal DNA of the E. granulosus sensu lato (s.l.)…”
Section: Investigation Of Close Family Members and Dogs Owned By The mentioning
confidence: 99%